Impaired Relaxation and Reduced Lusitropic Reserve in Atrial Myocardium in the Obese Patients - Wen, Yan; Deißler, Peter M.; Primeßnig, Uwe; Dushe, Simon; Falk, Volkmar; Parwani, Abdul Shokor; Boldt, Leif-Hendrik; Blaschke, Florian; Knosalla, Christoph; Grubitzsch, Herko; Pieske, Burkert M.; Heinzel, Frank R. (Frontiers in Cardiovascular Medicine, 2021)
Background: Obesity can influence the structure and function of the atrium, but most studies focused on the relationship of body mass index (BMI) and overt left atrium (LA) dysfunction as assessed by clinical imaging. We combined the assessment of right atrium (RA) function in vivo and in vitro in obese and non-obese patients scheduled for elective cardiac surgery. Methods: Atrial structure and function were quantified pre-operatively by echocardiography. RA tissue removed for the establishment of extracorporeal support was collected and RA trabeculae function was quantified in vitro at baseline and with adrenergic stimulation (isoproterenol). Fatty acid-binding protein 3 (FABP3) was quantified in RA tissue. Results were stratified according to the BMI of the patients. Results: About 76 patients were included pre-operatively for the echocardiographic analysis. RA trabeculae function at baseline was finally quantified from 46 patients and RA function in 28 patients was also assessed with isoproterenol. There was no significant correlation between BMI and the parameters of atrial function measured by the clinical echocardiography. However, in vitro measurements revealed a significant correlation between BMI and a prolonged relaxation of the atrial myocardium at baseline, which persisted after controlling for the atrial fibrillation and diabetes by the partial correlation analysis. Acceleration of relaxation with isoproterenol was significantly lower in the obese group (BMI ≥ 30 kg/m2). As a result, relaxation with adrenergic stimulation in the obese group remained significantly higher compared to the overweight group (25 kg/m2 ≤ BMI < 30 kg/m2, p = 0.027) and normal group (18.5 kg/m2 ≤ BMI < 25 kg/m2, p = 0.036). There were no differences on impacts of the isoproterenol on (systolic) developed force between groups. The expression of FABP3 in the obese group was significantly higher compared to the normal group (p = 0.049) and the correlation analysis showed the significant correlations between the level of FABP3 in the RA trabeculae function. Conclusion: A higher BMI is associated with the early subclinical changes of RA myocardial function with the slowed relaxation and reduced adrenergic lusitropy.